2015
DOI: 10.1016/j.ajpath.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Phenytoin-Induced Gingival Overgrowth by Lovastatin in Mice

Abstract: Drug-induced gingival overgrowth is caused by the antiseizure medication phenytoin, calcium channel blockers, and ciclosporin. Characteristics of these drug-induced gingival overgrowth lesions differ. We evaluate the ability of a mouse model to mimic human phenytoin-induced gingival overgrowth and assess the ability of a drug to prevent its development. Lovastatin was chosen based on previous analyses of tissue-specific regulation of CCN2 production in human gingival fibroblasts and the known roles of CCN2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
0
15
0
2
Order By: Relevance
“…We experimented using three drugs: first, a chemical chaperone 4phenyl butyric acid (4PBA) which is an ER stress antagonist. second, an antioxidant melatonin that we earlier noticed was attenuating AOPP levels in gingival fibroblasts: Assaggaf, Kantarci, Sume, and Trackman () observed statin inhibiting CTGF and EMT in mice phenytoin induced overgrowth. Based on this study report, we included simvastatin as the third drug.…”
Section: Introductionmentioning
confidence: 86%
“…We experimented using three drugs: first, a chemical chaperone 4phenyl butyric acid (4PBA) which is an ER stress antagonist. second, an antioxidant melatonin that we earlier noticed was attenuating AOPP levels in gingival fibroblasts: Assaggaf, Kantarci, Sume, and Trackman () observed statin inhibiting CTGF and EMT in mice phenytoin induced overgrowth. Based on this study report, we included simvastatin as the third drug.…”
Section: Introductionmentioning
confidence: 86%
“…Tissue blocks from three to five biopsies from different donors corresponding to dysplasia, differentiated OSCC, and poorly differentiated oral cancer, respectively, from the Boston University School of Dental Medicine Pathology diagnostic services laboratory were obtained under an approved IRB protocol (#31869). Sections (6 µm) were stained with hematoxylin and eosin, or immunostained for LOX or LOXL2 with counterstaining with hematoxylin 16,17 .…”
Section: Methodsmentioning
confidence: 99%
“…Alternative medications to the anticonvulsant phenytoin include carbamazepine and valproic acid, both of which have been reported to induce gingival enlargement to a lesser degree. A murine study suggested that lovastatin may attenuate the onset of gingival enlargement induced by phenytoin [28]. Further research is necessary to confirm the therapeutic value of lovastatin.…”
Section: Drug-induced Gingival Enlargementmentioning
confidence: 99%